Performance of bamboo and pvc as drainage materials in lowland soil - Coelho, Eugenio Ferreira; Pereira, Paulo Magela (Pesquisa Agropecuaria Brasileira, 1992)
The objetive of this work was to verify the usefulness of the bamboo (Bambusa tuldoides) and giant bamboo (Bambusa vulgaris) as drainage materials. Two drainage sistems were built: System 1 was set in a soil with saturated hydraulic conductivity of 0.58 m/day and drainable porosity of 4.9%. System 2, in a soil with the saturated hydraulic conductivity of 0.18 m/day drainable porosity of 2.9%. In system 1 three drainage materials were used: tied bundle bamboo, perforated corrugated PVC pipe and a furrow at the bottom of the ditch covered with bamboo sticks arranged across the furrow resulting in a drain similar to mole drain. In system 2 the drainage materials were: tied bundle bamboo, untied bundle bamboo, cut giant bamboo without septum at nodes and perforated corrugated PVC pipe. Each material was installed in three parallel ditches, 35 m long, 15 m apart and depth of 0.89 m. Water table depth, outflow from the drains and rainfall data were measured in the period from February, 1986 to March, 1988. Despite the best performance of untied bundle bamboo and the drains similar to mole drains using bamboo, all the bamboo arrangements tested were efficient as drainage materials.